Lifting barriers to skill transferability: Immigrant integration through occupational recognition - Silke Anger; Jacopo Bassetto; Malte Sandner (Rockwool Foundation Berlin (RF Berlin) and Centre for Research & Analysis of Migration (CReAM), 2024)
While Western countries worry about labor shortages, their institutional barriers to skill transferability prevent immigrants from fully utilizing foreign qualifications. Combining administrative and survey data in a difference-in-differences design, we show that a German reform, which lifted these barriers for non-EU immigrants, led to a 15 percent increase in the share of immigrants with a recognized foreign qualification. Consequently, non-EU immigrants' employment and wages in licensed occupations (e.g., doctors) increased respectively by 18.6 and 4 percent, narrowing the gaps with EU immigrants. Despite the inflow of non-EU immigrants in these occupations, we find no evidence of crowding out or downward wage pressure for natives.
Keywords: J24; J31; J62; F22; 330; Skill Transferability; Occupational Recognition; Immigrant Integration